Cell Type-Specific p38δ Targeting Reveals a Context-, Stage-, and Sex-Dependent Regulation of Skin Carcinogenesis - Kiss, Alexi (Int J Mol Sci, 2019)
Activation and/or upregulated expression of p38δ are demonstrated in human skin malignancies including cutaneous squamous cell carcinoma, suggesting a role for p38δ in skin carcinogenesis. We previously reported that mice with germline deletion of the p38δ gene are significantly protected from chemical skin carcinogenesis. Here, we investigated the effects of cell-selective targeted ablation of p38δ in keratinocytes and in immune (myeloid) cells on skin tumor development in a two-stage 7,12-dimethylbenz(a)anthracene (DMBA)/12-O-tetradecanoylphorbol-13-acetate (TPA) chemical mouse skin carcinogenesis model. Conditional keratinocyte-specific p38δ ablation (p38δ-cKO(∆K)) did not influence the latency, incidence, or multiplicity of chemically-induced skin tumors, but led to increased tumor volume in females during the TPA promotion stage, and reduced malignant progression in males and females relative to their wild-type counterparts. In contrast, conditional myeloid cell-specific p38δ deletion (p38δ-cKO(∆M)) inhibited DMBA/TPA-induced skin tumorigenesis in male but not female mice. Thus, tumor onset was delayed, and tumor incidence, multiplicity, and volume were reduced in p38δ-cKO(∆M) males compared with control wild-type males. Moreover, the percentage of male mice with malignant tumors was decreased in the p38δ-cKO(∆M) group relative to their wild-type counterparts. Collectively, these results reveal that cell-specific p38δ targeting modifies susceptibility to chemical skin carcinogenesis in a context-, stage-, and sex-specific manner.